The RC samples with infill walls strengthened with steel truss wires. (February 2022) - Kamil Akin, S.; Bahadir, Fatih; Süleyman Balik, Fatih; Turan, Mustafa
Abstract: Infilled walls are frequently used to create interior spaces in the reinforced concrete (RC) buildings and to provide heat and sound insulation. However, under earthquake loads, the infill walls resist the load and displacement demands that occur in and out-of-plane. Severe damages of masonry infill walls in many the reinforced concrete frames have been observed after the 2011 Turkey/Van-Ercis earthquake. It is aimed to strengthen the horizontal and vertical joints of the infill walls in order to increase the contribution of the infill wall to RC frame and to restrict the out-of-plane movement of the walls caused by the earthquake in the buildings. In this study, five RC frames used in the experimental works have been produced with various structural defects, 1/5 scale, two-story and one-bay. Two of these RC frames were filled with autoclaved aerated concrete blocks and brick wall. Other two samples were strengthened by adding truss elements to horizontal joints of infill walls. In order to determine the seismic contribution of these strengthening works, reference sample was tested as bare frame. All test samples were tested under reverse cyclic lateral loading and constant vertical loading. For the strengthened and non-strengthened samples with infill walls, the main damage occurred in the infill walls of the 1st storey at the experimental study. As a result, the sample with strengthened infill brick wall, and autoclaved aerated concrete block wall showed a significant increase in the lateral load-carrying capacities, initial stiffness, and the cumulative energy consumption capacity at the end of test.